CHOICE OF METHODS FOR ESTIMATING CHANGES IN PHOSPHATE И OF THE POTASSIUM STATE OF THE SOIL UNDER HUMAN INFLUENCE - I. Koroleva (Бюллетень Почвенного института им. В.В. Докучаева, 2010)
Expert assessment of methods for determining soil content Phosphorus and potassium used in soil science and agrochemistry to assess changes in the phosphate and potassium state of soils under anthropogenic impact. The principle of selection of methods was based on the necessity of strict coordination of research task, object of study (soil diversity) with real possibilities for analysis methods.